1996
DOI: 10.1159/000227594
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor and c-Met/Hepatocyte Growth Factor Receptor in Pulmonary Adenocarcinomas: An Evaluation of Their Expression as Prognostic Markers

Abstract: The expression of hepatocyte growth factor (HGF) and its receptor, c-Met, was investigated immunohistologically in tissue specimens of patients with a pulmonary adenocarcinoma. The prognosis was significantly worse in the HGF-positive or c-Met-positive patients than in the negative patients. Multivariate analysis showed that c-Met had a significant effect on the prognosis, whereas HGF did not. Our findings suggest that HGF and c-Met play an important role in tumor progression and that c-Met can be a useful pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 15 publications
1
62
1
Order By: Relevance
“…Furthermore, a connection between the positive expression of HGF-α or VEGF-C and shorter survival times in patients with NSCLC were observed. Other clinical studies of the HGF/c-Met pathway in NSCLC have also demonstrated an association with poor survival rates of NSCLC patients (31)(32)(33)(34). These findings, taken together, suggest that HGF-α, c-Met and VEGFC may serve as prognostic biomarkers in NSCLC.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, a connection between the positive expression of HGF-α or VEGF-C and shorter survival times in patients with NSCLC were observed. Other clinical studies of the HGF/c-Met pathway in NSCLC have also demonstrated an association with poor survival rates of NSCLC patients (31)(32)(33)(34). These findings, taken together, suggest that HGF-α, c-Met and VEGFC may serve as prognostic biomarkers in NSCLC.…”
Section: Discussionmentioning
confidence: 65%
“…MET is highly expressed in nonsmall cell lung cancer, 16,17,18 and its overexpression is associated with an advanced cancer stage and shorter patient survival. 17,18 Our group recently investigated the expression and activation of MET in lung adenocarcinoma tissues and cell lines.…”
Section: Japanmentioning
confidence: 99%
“…This requires further studies that use techniques to silence the HGF/SF expression and/or function. Recent reports indicated that a significant proportion of primary NSCLC overexpress HGF/SF and Met/HGFR (Harvey et al, 1996;Olivero et al, 1996;Takanami et al, 1996), and high levels of HGF/SF in these tissues may be correlated with a poor overall survival rate (Siegfried et al, 1997). The most important biological process that affects the survival or prognosis of lung cancer patients is metastasis, and cellular motility is one of the critical cellular functions during metastasis.…”
Section: Morphogenic Effect Of Hgf/sfmentioning
confidence: 99%